Order reduction for a system of stochastic differential equations with a small parameter in the coefficient of the leading derivative. Estimate for the rate of convergence - Bondarev, B. V.; Kovtun, E. E. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
In the metric $ρ(X, Y) = (\sup\limits_{0 ≤ t ≤ T} M|X(t) - Y(t)|^2)^{1/2} $for an ordinary stochastic differential equation oforder $p ≥ 2$ with small parameter of the higher derivative, we establish an estimate of the rate of convergence of its solution to a solution of stochastic equation of order $p - 1$.